The Roman Peasant Project 2009-2014 : Excavating the Roman Rural Poor - Bowes, Kimberly Diane (University Museum Publications, 2021)
Cover -- The Roman Peasant Project 2009-2014 Excavating the Roman Rural Poor -- VOLUME 1 -- Volume 1 Title -- Volume 1 Copyright -- Contents -- Author List -- Acknowledgments and Dedication -- Ceramic References and Abbreviations -- List of Figures -- List of Tables -- Part I: Old Questions and New Data -- 1 Introduction: Inventing Roman Peasants -- 1.1 Peasants: Definitions -- 1.2 Historiography I: Roman Peasant History and the Ancient Swerve -- 1.3 Historiography II: Archaeology and the Peasant Swerve -- 1.4 Project Questions and Hypotheses -- 1.5 Volume Outline -- 2 Methodologies -- 2.1 Precepts (KB) -- 2.2 Archeology in Roman Social History (KB) -- 2.3 Methodologies -- 2.3.1 Field Survey (MG) -- 2.3.2 Site Selection (KB) -- 2.3.3 Geophysics (MG) -- 2.3.4 Excavation (KB, MS) -- 2.3.5 Ceramics Analysis (EV) -- 2.3.6 Faunal Analysis (MM) -- 2.3.7 Land Analysis (AA) -- 2.3.8 Movement (AA, CG) -- 2.3.9 Geological Materials (AA) -- 2.3.10 Botanical Analysis (AMM) -- 2.3.11 Small Finds Analysis (SCE) -- 2.4 Quantification (KB) -- 3 Land and Locale -- 3.1 Locale (KB, CG) -- 3.2 Land (AA) -- 3.3 Vegetation (ER) -- 3.4 Human Activity in a "Liminal" Landscape (KB) -- 3.5 Human Activity in the Commune of Cinigiano (KB, MG) -- 3.6 Characteristics of the Locale (AA, KB, MG) -- 3.7 Conclusions (KB) -- Excavations -- 4 Pievina -- 4.1 Situation (AA, MG) -- 4.2 Remote Sensing (MG) -- 4.3 Excavation (KB) -- 4.4 Chronology (EV) -- 4.5 Ceramics (EV) -- 4.6 Faunal Materials (MM) -- 4.7 Geological Considerations, Land Units, and Evaluation (AA) -- 4.8 Botanical Materials -- 4.9 Coins (FM) -- 4.10 Small Finds (SCE) -- 4.11 Glass (SCE, ERR) -- 4.12 Building Materials (AA) -- 4.13 Discussion (KB) -- 5 Case Nuove -- 5.1 Situation (AA, CG, EV) -- 5.2 Remote Sensing (MG) -- 5.3 Excavation (KB) -- 5.4 Residue Analysis (AP, MACO).